Resurrection and redescription of Liolaemus reichei, proposal of a neotype to stabilize its taxonomy - Pablo Valladares-Faúndez; Richard Etheridge; Cristián Simón-Abdala (Revista Mexicana de Biodiversidad)
Liolaemus reichei was described by Werner and published by Otto Bürger in 1907 on the basis of 1 specimen captured in Iquique, Chile. The taxonomy of this species has been controversial, because it was originally placed in the genus Phrynosaura and was recently synonymized with Liolaemus stolzmanni based on a picture of the syntype of the latter species. We have identified a set of diagnostic characters that distinguish L. reichei from L. stolzmanni. Because there has been persistent confusion regarding the identity and the existence of the taxon described by Werner, we here resurrect, redescribe and designate a neotype of this species to stabilize the taxonomy of Liolaemus reichei. This work is based on specimens that were captured near Iquique, Chile, and is consistent with the original description.